O impacto do fundo Amazônia para o fortalecimento de organizações da sociedade civil (OSC) amazônicas brasileiras - Costa, Maria Gessica Silva da (2024)
Environmental degradation and climate change have become more worrying in recent years, prompting global discussions aimed at devising solutions to reverse these trends. One of the alternatives aiming to have a positive impact on the environmental situation is the Amazon Fund, which operates as a mechanism receiving donations from various countries in the process of North-South Cooperation. These funds are allocated to projects implemented by diverse organizations, including Civil Society Organizations (CSOs). Thinking about the effectiveness of the participation of these organizations in achieving the Fund's objective, CSOs have great potential to develop actions with positive socio-environmental impacts, however, they often face limitations due to insufficient institutional sustainability. Therefore, this study aims to analyze whether the Amazon Fund, through its Calls for Proposals, contributes to the institutional strengthening of CSOs in the Brazilian Amazon region. This research has a qualitative approach, is descriptive and exploratory, and is configured as a case study, bibliographic and documentary in terms of technical procedures, in which a case study examines 6 published Calls for Proposals by the Amazon Fund to identify 3 dimensions of institutional development: financial, technical-managerial, and socio-political. Finally, for data analysis and interpretation, content analysis was applied. The analysis reveals that the public calls bring potential contributions and stipulated requirements within the 3 areas, with the contributions being mainly in the socio-political area, and the requirements in the technical-managerial area. These contributions include financial resources for structures, equipment and some administrative costs, training incentives, operational and managerial technical assistance, knowledge production and transparency initiatives, support services and studies aimed at strengthening the locality. Moreover, they encourage participation in public policies, partnerships, collaborative efforts with diverse stakeholders, and strengthening of other CSOs, the public sector, and local communities. The requirements include fiscal and financial regularity, provision of matching funds, regularization of CSO establishment, proficiency in bureaucratic procedures, financial management, good governance, participatory decision-making process, historical, successful experiences, support to project stakeholders, coordination of stakeholders and comprehensive planning, monitoring, and evaluation frameworks. In conclusion, the study suggests that the Amazon Fund, through Calls for Proposals, promotes institutional development primarily in the socio-political area, contributing to both local and organizational strengthening. However, However, stringent requirements pose challenges for smaller organizations lacking financial resources, experience, and administrative expertise. A large part of the funds resources are allocated to a small number of institutions, indicating a preference for financing developed entities, capable of coordinating collaborative initiatives and sub-projects. Therefore, for smaller organizations to effectively access Amazon Fund resources, collaboration with larger aggregating institutions appears to be a viable strategy.